Queer is God - Murphy, Murph (Concilium, 2019)
This text explores the experience of Murph, a non-binary queer identified white person, raised in a conservative Catholic community in the United States of America. They came to embrace their queerness through community, movement, and dancing. Murph explains the way they feel and act queer as a divine form of resistance, creation, and expression of life.